Development of a high‐throughput crystal structure‐determination platform for JAK1 using a novel metal‐chelator soaking system. Issue 11 (9th November 2016) - Caspers, Nicole L.; Han, Seungil; Rajamohan, Francis; Hoth, Lise R.; Geoghegan, Kieran F.; Subashi, Timothy A.; Vazquez, Michael L.; Kaila, Neelu; Cronin, Ciarán N.; Johnson, Eric; Kurumbail, Ravi G.
Abstract : Active JAK1 kinase domain was crystallized with MgADP and soaked in the presence of EDTA to allow displacement of the nucleotide by compounds of interest. This high‐throughput method of structure determination may be widely applicable to other protein kinases and small‐molecule ATP‐competitive ligands. Abstract : Crystals of phosphorylated JAK1 kinase domain were initially generated in complex with nucleotide (ADP) and magnesium. The tightly bound Mg 2+ ‐ADP at the ATP‐binding site proved recalcitrant to ligand displacement. Addition of a molar excess of EDTA helped to dislodge the divalent metal ion, promoting the release of ADP and allowing facile exchange with ATP‐competitive small‐molecule ligands. Many kinases require the presence of a stabilizing ligand in the ATP site for crystallization. This procedure could be useful for developing co‐crystallization systems with an exchangeable ligand to enable structure‐based drug design of other protein kinases.